The impact of the synthesis conditions on SrAl2O4:Eu, Dy formation for a persistent afterglow. (15th October 2016) - Rojas-Hernandez, Rocío Estefanía; Rubio-Marcos, Fernando; Dos Santos Rezende, Marcos Vinícius; Rodriguez, Miguel Ángel; Serrano, Aida; Muñoz-Noval, Álvaro; Fernandez, José Francisco
Abstract: The design of phosphorescent materials, highly crystalline, with a submicron particle size is a challenge for industrial applications. Based on molten salt assisted process, the effects of salt/SrAl2 O4 molar ratio on the phase evolution are studied. A significant influence of salt/SrAl2 O4 molar ratio on synthesis and final properties has been observed. Moreover, the phase evolution has been explored as a function of treatment temperature. To remove the salt from the powder, the wash step is carried out with glycerin avoiding hydrolysis reaction due to the sensitivity of strontium aluminates to water. The salt/SrAl2 O4 molar ratio of 3:1 and the thermal treatment at 1000 °C are preferred, avoiding extra wash step. Here, we have obtained highly crystalline SrAl2 O4 :Eu 2 +, Dy 3 + powder with a particle size ≤ 0.5 μm after a 2 h treatment at 1000 °C employing the molten salt approach. As a result, we believe that the general strategy described in this study opens the possibility of obtaining technologically relevant phosphors with enhanced properties, expanding their application range to radiation detection. Graphical abstract: Highlights: Optimal conditions were established to synthesize SrAl2 O4 :Eu, Dy sub-micron particles by molten salt assisted process. A significant influence of salt/SrAl2 O4 molar ratio on synthesis and final properties has been observed. This approach provides the conditions to obtain persistent luminescent particles in one step process at low temperatures. Molten salt route proposed could offer a straightforward alternative for technologically relevant phosphorescent powders.